Effect of Acetic Acid Pretreatment on Hydro-extraction of Water-Soluble Collagen from Skin of Alaska Pollock (Theragra chalcogramma) - Patmawati; Aliffiansyah Rizky Ergion; Laksmi Sulmartiwi; Raseetha Vani Siva Manikam; Dwitha Nirmala; Yaowapha Waiprib; Sapta Wijayanti (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research The optimal condition for production of water-soluble collagen from Alaska pollock fish skin was the pretreatment with 0.15 M acetic acid followed by hydro-extraction at 40oC with 150 rpm for two hours. Higher acetic acid concentration at a pretreatment step enhanced the higher yield of water-soluble collagen via hydro-extraction process. Hydro-extraction was an environmentally friendly method for converting Alaska pollock fish skin to water-soluble collagen. Alaska pollock fish skin could be used as an alternative source for collagen production. Abstract To date, there is no information on skin of Alaska Pollock (Theragra chalcogramma) being used as a source for collagen. In order to produce water-soluble collagen from the skin of Alaska Pollock, a process known as hydro-extraction is utilized. This technique does not need a long extraction time or a large amount of chemical reagent. The purpose of this study was to investigate the effect of acetic acid pretreatment on hydro-extraction of water-soluble collagen from Alaska Pollock skin. The skin samples were pretreated using acetic acid at different concentrations (0.01 M; 0.05 M; 0.1 M, 0.15 M) for two hours at chilling temperature. The pretreated skin samples were further processed to produce water-soluble collagen using the hydroxy-extraction method. The obtained collagen was analyzed for proximate compositions, yield, and amino acids compositions with high performance liquid chromatography. It was found that the proximate compositions of the collagen products, specifically the protein content (75%) and fat content (1%), met the requirements of the Indonesian National Standard (SNI 8076:2014). The collagen yield ranged from 2.6 to 3.13%. The predominate amino acids in collagen were glycine, arginine, proline, glutamic acid, serine, and alanine. Pretreatment of skin sample with 0.15 M acetic acid resulted in the highest yield of water-soluble collagen (3.13%) and protein content (91.13%). The skin of Alaska Pollock fish could be used as an alternative raw material to produce water-soluble collagen for medical, pharmacy or food processing applications.